2021
DOI: 10.1002/ijgo.13552
|View full text |Cite
|
Sign up to set email alerts
|

FIGO good clinical practice paper: management of the second stage of labor

Abstract: This good clinical practice paper provides an overview of the current evidence around second stage care, highlighting the challenges and the importance of maintaining highquality, safe, and respectful care in all settings. It includes a series of recommendations based on best available evidence regarding length of second stage, judicious use of episiotomy, and the importance of competent attendants and adequate resource to facilitate all aspects of second stage management, from physiological birth to assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…World Health Organization (WHO) Guideline Developing Groups emphasized the need for health systems to adopt a policy of restrictive rate of not more than 10% rather than routine use of episiotomy to reduce its potential complications and the use of additional resources for its treatment [14] as restrictive episiotomy has shown benefits [15]. Restrictive other than routine episiotomy protocol has been supported by FIGO [16], a mediolateral episiotomy type is the one recommended, and this should be performed under adequate analgesia, whether anesthesia is already in place for labor, such as epidural, or by administering a local infiltration [16].…”
Section: Current Trend In Episiotomy Practicementioning
confidence: 99%
“…World Health Organization (WHO) Guideline Developing Groups emphasized the need for health systems to adopt a policy of restrictive rate of not more than 10% rather than routine use of episiotomy to reduce its potential complications and the use of additional resources for its treatment [14] as restrictive episiotomy has shown benefits [15]. Restrictive other than routine episiotomy protocol has been supported by FIGO [16], a mediolateral episiotomy type is the one recommended, and this should be performed under adequate analgesia, whether anesthesia is already in place for labor, such as epidural, or by administering a local infiltration [16].…”
Section: Current Trend In Episiotomy Practicementioning
confidence: 99%
“…Two papers in this issue touch on this important topic. In the first, 10 The final good clinical practice paper that addresses issues related to the second stage of labor 12 is an update of the FIGO SMNH Committee's paper published in IJGO in 2012. 13 Although not intended to be a systematic review of the literature, it is rather a document to strengthen frameworks for service provision and to enable healthcare providers to improve intrapartum care for women, in line with evidence-based recommendations.…”
Section: A Framework For Safe Obstetrical Practicesmentioning
confidence: 99%
“…Prolonged second stage has been extensively studied, showing associations with an increased risk of operative delivery, post-partum haemorrhage (PPH), obstetric anal sphincter injury (OASI) and adverse neonatal outcomes [ 3 11 ]. There is no worldwide consensus regarding the definition of prolonged second stage and international organizations vary in their recommendations [ 12 14 ]. However, the two different phases in the second stage have not been separated in most studies and recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Obstetricians and Gynaecologists has acknowledged that the second stage contains two phases, but does not provide any recommendations regarding the appropriate definition for a prolonged passive phase [ 20 ] and The International Federation of Gynecology and Obstetrics has identified a need for targeted research into the duration of the passive and active second stage and maternal and fetal outcomes [ 12 ]. A few previous studies have showed differences in birth outcomes regarding the duration of the passive second stage [ 21 , 22 ] but this area needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%